Staro telo v sociološki teoriji - Krpič, Tomaž (Teorija in praksa, 2011)
This article discusses selected themes and problems in the sociology of the ageing body, including: the absence of the ageing body concept, the significance of biomedicine, representations of the ageing body, and the active ageing body. Feminist sociologists (of the body) are found to be leading the field, while their male colleagues are more or less lagging behind. Further, this paper asserts that the field of the ageing body is theoretically underdeveloped since the existing works are mainly empirical in nature. Foucault's discursive theory is clearly the predominant framework used by researchers. However, the phenomenological experience of the ageing body is gradually moving into the field. In addition, the article highlights the finding that most ageing body researchers are pessimistic as regards the potential for a positive outcome of the struggle against ageism in the future.
Keywords: Človekovo telo; Human body; Ageing; Staranje; Sociološke teorije; Sociological theories; človeško telo; starost; sociološke raziskave